Entrepreneurial Education Mediates Entrepreneurial Intention among Dietetics Students in Malaysia - Kok, Ee Wei Kok; Binti Noor Khilmi, Nur Khairina; You, Yee Xing; Mazri, Fatin Hanani; Manaf, Zahara Abdul (Jurnal Gizi dan Pangan, 2025)
This study aimed to determine entrepreneurship intention, the factors that influence it, and the mediation effect of entrepreneurship education among undergraduate dietetics students in Malaysia. This cross-sectional study used a purposive sampling method and was conducted online among 221 Malaysian dietetics students from eight Higher Education Institutions (HEIs) in Malaysia. The validated questionnaire contained 30 items with 5 domains: attitude towards entrepreneurship, perceived behaviour control, entrepreneurship education, entrepreneurship intention, and self-efficacy. Descriptive analysis, Spearman's rho non-parametric test, and mediation analysis were performed to examine the relationships among the variables and the potential mediating effects. This study found positive and significant relationships between entrepreneurial attitude, perceived behaviour control, entrepreneurship education, self-efficacy, and entrepreneurship intention (p<0.001). Furthermore, entrepreneurial education partially mediates the link between entrepreneurial attitude, self-efficacy, and perceived behaviour control toward entrepreneurship intention. This study suggests the incorporation of an entrepreneurship education program into the curriculum and the encouragement of entrepreneurial activities among dietetics students in higher education institutions in Malaysia.